Draft Eighth Five Year Plan 1990-95 Volume II General Areas Government of Assam - Planning Commission (Planning Commission, 1990)
It is, therefore, evident that the year 1985-86 was a good year for agriculture in the State and it has not been possible, as yet, to surpass the production levels achieved in that year. This is primarily because, whereas the State either had to suffer several waves of floods or experience a fairly long spell of drought followed by late flood in almost all the years, natural calamities did not create the usual havoc in 1985-86.
Government of Assam, Planning and Development Department